The Query Of The Sanctions For Enforcement Of Money Politics In Indonesia - Mirawati Saktiana; Zudan Arif Fakhrulloh (Faculty of Law, University of Mataram, 2022)
General elections, which are held on a regular basis to elect leaders in a country, are a sign of a democracy. The ruling of the Constitutional Court, which specifies that elections in Indonesia be held concurrently, both national and local elections, undoubtedly produces dynamics and obstacles in election administration. It is evident that the practice of electoral fraud is inextricably linked to the conduct of elections in Indonesia. Starting with indirect elections, Indonesia has now moved on to direct elections. Because the execution is simultaneous and simultaneous, the concentration of election organizers and supervisors is split. Although there is already an Election lAW that regulates law enforcement for election offenses, the existence of these provisions is regarded ineffective and inefficient in areas where there are still numerous frauds in elections, including money politics. This paper will look at the regulation of vote buying (money politics) and how sanctions are used. Using primary, secondary, and tertiary legal texts, this study employs a normative legal writing technique. This study concludes that the regulation of criminal punishments in money politics fraud has been regulated in Elections Law Number 7 of 2017. Although infractions of legal politics are restricted under the a quo Law, these arrangements have not been totally effective in limiting the degree of election violations and crimes, particularly money politics. As a result, it should be reconsidered by considering other administrative fines for political parties or candidate candidates in order to offer a greater deterrent impact.